Evidencing the magnetoelectric coupling in Bi1-xNdxFeO3 compositions through ferroic characterizations. Issue 174 (1st September 2016) - Mincache, A. J.; Oliveira, O. G.; Silva, D. M.; Santos, G. M.; Dias, G. S.; Santos, I. A.; Cótica, L. F.; Guo, R.; Bhalla, A. S.
ABSTRACT: The study of multiferroic crystalline materials is of great technological and academic interest due to the correlation between their ferroelectric and ferromagnetic properties. In this work, ferroic properties of Nd-modified (A-site substitution) BiFeO3 (BNFO) compounds were studied. Ceramic compositions of Bi1-x Ndx FeO3 (x = 0.10 and 0.20) were obtained through a route that included high-energy ball milling, isostatic pressing (to obtain the ceramic shape) and sintering in air. The X-ray diffraction data showed that these compositions have a distorted perovskite structure, with relative densities reaching 93%. Dielectric measurements showed a frequency independent step-like relaxation for the Bi0.9 Nd0.1 FeO3 composition and indicatives indications of thermally activated conduction processes for the Bi0.8 Nd0.2 FeO3 composition. Magnetic studies showed a breakdown of the typical magnetic cycloidal structure of BiFeO3 .